Further enhancement of the particle shifting technique: Towards better volume conservation and particle distribution in SPH simulations of violent free-surface flows - Lyu, Hong-Guan; Sun, Peng-Nan (Applied Mathematical Modelling, 2022)
•An enhanced particle shifting technique (PST) is presented to overcome the deficiencies of traditional PSTs.•The volume-non-conservation issue is tackled by introducing a corrective cohesion force between particles.•The non-physical gap issue is alleviated by introducing a different free-surface treatment.•Four benchmarks are implemented to validate the effectiveness and stability of the present scheme.•Satisfactory numerical results are obtained in WCSPH simulations of violent free-surface flows. [Display omitted] The non-conservation of total fluid volume, caused by the accumulating errors on the potential energy of the fluid, has been a serious numerical issue in a Weakly-Compressible SPH (WCSPH) simulation when transitional Particle Shifting Techniques (PSTs) are employed to prevent disordered particle distribution and the tensile instability from negative pressures. This paper is dedicated to, within the framework of WCSPH, developing an enhanced version that remedies the aforementioned deficiency of the traditional PSTs, and meanwhile improves the quality of the particle distribution in the vicinity of a free-surface region. To this end, a Corrective Cohesion Force (CCF) between a target particle and its interacting particles is introduced to provide adaptive compensation corresponding to the particle repositioning. Four classical benchmarks are implemented to validate the effectiveness and stability of the present PST. It is demonstrated that the new PST incorporating with the CCF shows satisfactory performance to improve the conservation of total fluid volume, and to obtain more uniform particle distribution in the proximity of the free-surface. In addition, the newly-developed PST also maintains the accuracy and stability inherited from the traditional versions, suggesting that it can be treated as an ideal alternative with regard to the traditional PSTs in a WCSPH simulation, especially for a long-term-duration case with violent free-surface evolutions.